Apolipoprotein E as Risk Factor for Coronary Heart Disease - Pramudji Hastuti; Abdul Salam M. Sofro; Ahmad Husain Asdie; Ahmad Hamim Sadewa (Indonesian Journal of Biotechnology, 2013)
Allelic variation of apolipoprotein E (apo E) has been shown to infl uence the concentrations of total cholesterol and low density lipoprotein cholesterol (LDL-C) and considered to play a role as one of risk factors for coronary heart disease (CHD). The aim of this study was to examine the relationship between Apo E polymorphism and the risk of CHD. Blood samples were collected from 33 CHD patients in Dr. Sardjito Hospital Yogyakarta, and 38 apparently healthy control individuals in a cross sectional study. The common allelic variants of ApoE were screened employing polymerase chain reaction and restriction fragment length polymorphism. The results obtained were analyzed by t-test and signifi cantly different if p <0.05 and risk factor was calculated by odd ratio. Frequency of ApoE ε2, ε2 and ε4 alleles in CHD patients were 12.1%, 69.7% and 18.2% while in controls were 18.4%, 72.4% and 9.2% respectively. Dyslipidemia condition was a strongrisk factor for CHD. By controlling lipid profi le and applying multifactorial statistic analysis, it was shown that ε4 gene carrier was the risk factor for CHD, but not in triglyceride level, whereas ε2 carrier gene was not the risk factor for CHD. Dislipidemia was the risk factor for CHD and ApoE ε4 gene carrier was the risk factor for CHD. Key words: apolipoprotein E, ApoE ε4 gene carrier, coronary heart disease, dyslipidemia.